Looking for Pyroptosis-Modulating miRNAs as a Therapeutic Target for Improving Myocardium Survival - Seahyoung Lee; Eunhyun Choi; Min-Ji Cha; Ki-Chul Hwang (Mediators of Inflammation)
Pyroptosis is the most recently identified type of regulated cell death with inflammatory response and has characteristics distinct from those of apoptosis or necrosis. Recently, independent studies have reported that small noncoding RNAs termed microRNAs (miRNAs) are involved in the regulation of pyroptosis. Nevertheless, only a handful of empirical data regarding miRNA-dependent regulation of pyroptosis is currently available. This review is aimed to provide a current update on the role of miRNAs in pyroptosis and to offer suggestions for future studies probing miRNAs as a linker connecting pyroptosis to various cardiovascular diseases (CVDs) and their potential as a therapeutic target for preventing excessive cell death of myocardium during CVDs.